Legal Protection For Online Transportation Drivers In The Case Of Fictional Order In Indonesia - Denden Adith Fauzan; Yana Sukma Permana (IHSA Institute, 2022)
The development of technology and information has penetrated all aspects of life, one of which is the problem of transportation. Transportation is an important aspect for humans in their activities. Changes in the mass transportation system infiltrated by technological sophistication make conventional methods gradually abandoned. There are several companies that provide online transportation services due to the changing times that humans use for time efficiency and effectiveness. Among them are Gojek, Grab, and Maxim who have contributed greatly to helping the community's economy by creating millions of jobs. Behind the benefits that the company presents to partners and consumers, there is a serious problem that occurs, namely the existence of fictitious orders from several unscrupulous consumers that harm drivers. This study aims to unravel the problem of fictitious orders that occur and how the legal protection for the driver is related to the case that happened to him. The conclusion is that the company's efforts to protect drivers are only limited to solving problems internally. There has been no firm action in eradicating rogue consumers because if this continues, it will disrupt the performance of driversitself. Online transportation service companies must immediately evaluate services and make SOPs that are not only preventive in nature but also repressive in resolving cases firmly and thoroughly as regulated in the Civil Code and the Consumer Protection Law.